2003
DOI: 10.4049/jimmunol.170.10.5235
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic Factor-Induced Recruitment and Activation of Tec Family Kinases in Human Neutrophils. II. Effects of LFM-A13, a Specific Btk Inhibitor

Abstract: Tyrosine phosphorylation events play major roles in the initiation and regulation of several functional responses of human neutrophils stimulated by chemotactic factors such as the bacterially derived tripeptide formylmethionyl-leucyl-phenylalanine (fMet-Leu-Phe). However, the links between the G protein-coupled receptors, the activation of the tyrosine kinases, and the initiation of neutrophil functional responses remain unclear. In the present study we assessed the effects of a Btk inhibitor, leflunomide met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 54 publications
(48 reference statements)
7
63
0
1
Order By: Relevance
“…We have shown that IL-8 treatment induces membrane translocation of Btk. Furthermore, after adding LFM-A13, an inhibitor of Btk, we observed the inhibition of the IL-8-induced activation of the MAPK and Akt/PKB pathways reminiscent of previous results obtained after fMLP stimulation (31). LFM-A13 also inhibited both p47 phox and p67 phox phosphorylation induced by IL-8 treatment.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We have shown that IL-8 treatment induces membrane translocation of Btk. Furthermore, after adding LFM-A13, an inhibitor of Btk, we observed the inhibition of the IL-8-induced activation of the MAPK and Akt/PKB pathways reminiscent of previous results obtained after fMLP stimulation (31). LFM-A13 also inhibited both p47 phox and p67 phox phosphorylation induced by IL-8 treatment.…”
Section: Discussionsupporting
confidence: 64%
“…On the basis of the effects of the inhibitors tested (genistein and wortmannin), we showed that the IL-8-induced phosphorylation of both p47 phox and p67 phox depended on the upstream activation of tyrosine kinase and PI3K. Among the tyrosine kinases, the Tec kinases, and especially Btk has recently been shown to be involved in fMLP signaling, thus providing a direct link between G protein-coupled receptors and activation of the tyrosine kinases (31). Activation of the Tec kinases is mediated in part by the high affinity of their pleckstrin homology domains for phosphatidylinositol 3,4,5-P 3 (50), which is generated following the activation of PI3K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the Tec family nonreceptor tyrosine kinases, Btk and Tec, in bt/VWF-induced signaling in platelets was investigated because of the close relationship between PI3K and Btk in signal transduction in B cells, 17,18 neutrophils, 39 and platelets 19,40 and because previous work from this laboratory demonstrated that bt/VWF-induced TxA2 production is inhibited by the PI3K selective inhibitor wortmannin. 14 Furthermore, Btk plays an important role in PLC␥ activation, [20][21][22][23] and PLC␥ is required for bt/VWFinduced TxA2 production.…”
Section: Evaluation Of the Role(s) Of Btk In Txa2 Production Elicitedmentioning
confidence: 99%
“…We focused on three, WMN because of the known involvement of PI3K in lymphocyte chemotaxis [8,9], LFM-A13 because of the importance of Bruton's tyrosine kinase (Btk) in B lymphocyte function and recent demonstration of its role in neutrophil chemotaxis [22], and JNK because of its known role in the migration of other cell types [19,20].…”
Section: Introductionmentioning
confidence: 99%